Fermentation of Tacca leontopetaloides starch with ragi tapai for bioethanol production / Suhaila Mohd Sauid ... [et al.] - Mohd Sauid, Suhaila; Ab Wahab, Muhamad Afiq; Jamian, Mohamad Mohd Aliff; Mat Zain, Ahmad Fahmi; Mustafa, Herlina (Universiti Teknologi MARA Shah Alam, 2023)
This study investigates the potential of Tacca leontopetaloides starch as an alternative raw material for bioethanol production. Ragi tapai was used as the saccharification and fermentation agent and different origin of ragi tapai was evaluated for the highest glucose production. Ragi tapai from Sabah (RTSab) produced significantly higher glucose as compared to other origins of ragi tapai and was then used in the rest of the study. Fermentation of ragi tapai with T. leontopetaloides starch was compared with the fermentation of ragi tapai - Saccharomyces cerivisiae co-culture. Glucose and ethanol concentrations were measured by spectrophotometric method. It was found that ragi tapai alone is more efficient in producing bioethanol as the concentration was the highest (17.4% v/v) with productivity reaching 4.5 g/l/h in comparison to only 3.7 g/l/h for co-culture fermentation. Glucose concentration also varied at higher level throughout the fermentation and peaked at 84.28 g/L. This study concludes that T.leontopetaloides starch is a potential raw material for bioethanol and use of ragi tapai is effective in producing bioethanol.